EXPLORATION OF ANTI-MELANOMA POTENTIAL OF PHYTOCHEMICALS FROM NYCTANTHES ARBORTRISTIS THROUGH COMPUTATIONAL STUDIES - BANERJEE, SHARMISTHA; BHARKATIYA, MEENAKSHI; PRAKASH RAO, SURADA; BAGHEL, ISHITA; BAGHEL, MADHURI (International Journal of Applied Pharmaceutics, 2024)
Objective: The goal of the current research is to identify the dominant phytochemical from the plantNyctanthesarbor-tristis Linn. and to investigate their binding affinities against the proteins BRaf Kinase mutant (3OG7) and Hsp90 Chaperone (2VCJ) that causesmelanoma. Methods: In this work, Schrodinger software was utilized to investigate the anti-cancer potential of phytochemicals Nyctanthesarbor-tristis against specific target proteins, namely BRaf Kinase mutant (3OG7) and Hsp90 Chaperone (2VCJ) Inhibitors. Results: Based on the outcome of the docking investigation, phytochemicals that exhibited highest binding affinity to the specified protein targets were subjected to induced fit docking and MM-GBSA computations using the Schrodinger Maestro version 2021.2 in prime module. According to the analysis, the compounds with the highest binding affinities for 2VCJ and 3OG7 are Arbortristoside D and Nicotiflorin respectively. The compound that interacted with both the proteins wasArbortristoside B. These phytochemicals appear to be more effective to the FDA-approved V600E-BRaf inhibitor Vemurafenib and Hsp90 Chaperone Inhibitor Diclonine. Conclusion: One of the most common, deadly, and dangerous malignant diseases with a high global prevalence rate is melanoma (skin cancer). The present study may prove more helpful in developing an ideal targeted drug delivery system of phytochemicals obtained from plant Nyctanthesarbor-tristisfor treatment of melanoma. This suggests that these substances could be evolved into highly effective anti-melanoma drugs.